Associations between overweight/obesity and physical fitness variables in Korean women - Kim, Jong-Hyuck; So, Wi-Young (Central European journal of public health, 2013)
AIM: The purpose of this study was to investigate whether physical fitness variables are related to overweight or obesity in Korean women. METHODS: From 2007 to 2011, 10,790 women aged 20-82 years visited a public health centre for evaluation of cardiovascular function, health-related physical fitness, and motor-related physical fitness. We used the definitions of overweight and obesity provided in the World Health Organization's Asia-Pacific Standard Report. Cardiovascular function was evaluated using the Resting Heart Rate (RHR) and vital capacity. Health-related physical fitness was evaluated using the VO2max measure, sit-up number, grip strength, and sit-and-reach distance. Motor-related physical fitness was evaluated using the vertical-jump distance, side-step number, and balance (standing on 1 foot with eyes open) measure. RESULTS: The prevalence rates of overweight and obesity were 26.9% and 28.8%, respectively. Results are presented as odds ratios (with 95% confidence intervals) after adjusting for age and number of alcoholic drinks consumed per week, cigarettes smoked per day, and exercise sessions per week. When RHR increased by 1 beat per minute, overweight prevalence was 1.012 times higher (1.007-1.017, p < 0.001) and obesity prevalence was 1.006 times higher (1.000-1.011, p = 0.037). When VO2max increased by 1 mL x kg(-1) x min(-1), overweight was 0.949 times less prevalent (0.939-0.959, p < 0.001), and obesity was 0.916 times less prevalent (0.906-0.926, p < 0.001). As grip strength increased, overweight prevalence and obesity prevalence increased. An increase in vertical-jump distance by 1 cm was accompanied by a decrease in overweight prevalence by a factor of 0.975 (0.967-0.982, p < 0.001) and a decrease in obesity prevalence by a factor of 0.940 (0.932-0.948, p < 0.001). CONCLUSION: Overweight and obesity were associated with poor physical fitness as assessed by variables related to cardiovascular function and health-related and motor-related physical fitness.
Keywords: dospělí; Body Weights and Measures; Female; Overweight; Prevalence; Korejská republika; Adult; mladý dospělý; ženské pohlaví; Republic of Korea; Physical Fitness; tělesná výkonnost; Obesity; funkční vyšetření srdce; lidé; tělesné váhy a míry; cvičení; Aged, 80 and over; Humans; prevalence; zdravé chování; obezita; Aged; Young Adult; nadváha; Heart Function Tests; lidé středního věku; senioři nad 80 let; senioři; Exercise; Middle Aged; Health Behavior